Comparison of gluten peptides and potential prebiotic carbohydrates in old and modern Triticum turgidum ssp. genotypes. (June 2019) - Ficco, Donatella Bianca Maria; Prandi, Barbara; Amaretti, Alberto; Anfelli, Igor; Leonardi, Alan; Raimondi, Stefano; Pecchioni, Nicola; De Vita, Pasquale; Faccini, Andrea; Sforza, Stefano; Rossi, Maddalena
Abstract: Old wheat genotypes are perceived by consumers as healthier than modern ones. The release of gluten peptides with in vitro digestion and the content of potentially prebiotic carbohydrates ( i.e. resistant fraction of starch and cell-wall associated dietary fiber) were evaluated in tetraploid wheats, namely 9 old and 3 modern Triticum turgidum ssp. genotypes . Simulated digestion of wholemeal flours yielded 152 major peptides, 59 of which were attributed a sequence. Principal component analysis revealed that peptide profiles were variable in old genotypes, unlike in modern ones. Digestion of old genotypes generally yielded peptides in greater concentration. In particular, 5 peptides of γ-gliadin, known to trigger the adaptive immune reaction, and two peptides of α-gliadin, known to be toxic to celiac patients, were particularly abundant in some old varieties. Resistant starch (RS) was negligible in modern genotypes (<0.6%), but it was remarkably abundant in some old varieties, reaching the highest value in Dauno III (8.5%, P  < 0.05). Dauno III also presented the highest amount of soluble fiber (4.2%, P < 0.05). Pasta was made with an old and a modern genotype (Dauno III and PR22D89, respectively) with opposite RS content. Pasta making and cooking affected starch digestibility, overtaking differences between genotypes and yielding the same amount of RS for both the varieties (approx. 1.7%). The data herein presented suggest that the wholemeal flours of old tetraploid wheat genotypes could not boast particular claims associated to a lower exposure to gluten peptides and, if cooked, to a prebiotic potential. Graphical Abstract: Unlabelled Image Highlights: Gluten peptides, fiber, and starch were analyzed in old and modern wheat genotypes. Peptides associated to celiac disease were released abundantly in some old genotypes. Resistant starch is abundant in the wholemeal of some old wheat genotypes. Pasta cooking overtook differences in resistant starch content between genotypes. Old wheats cannot claim prebiotic potential or low gluten compared with the new ones.